Preparation of a porous hydroxyapatite-carbon composite with the bio-template of sugarcane top stems and its use for the Pb(II) removal. (20th June 2018) - Zhu, Yinian; Jiang, Yanhong; Zhu, Zongqiang; Deng, Huan; Ding, Hui; Li, Yanhong; Zhang, Lihao; Lin, Ju
Abstract: A mature crop of sugarcane produces large amount of residue at harvest in the form of tops. The aim of the present work was to use the discarded tops of harvested sugarcane as a potential raw material for the removal of heavy metals from aqueous solution. A hydroxyapatite-carbon adsorbent with the hierarchical porous microstructure of sugarcane stems (SS-HAP/C) was prepared by carbonizing stem internodes of sugarcane tops and subsequent doping with the saturated limewater solution and 0.02 mo1/L (NH4 )2 HPO4 solution in turn for five times. The morphological character of SS-HAP/C was inherited from the bio-precursors of sugarcane top stems, which mainly included the macropores from the storage parenchyma thin-walled cells of 30–115 μm in width, the parallel and densely packed vessels of 20–85 μm in width, the sclerenchyma thick-walled cells of ∼30 μm in width, and the pits in the vessel and cell walls of about ∼4.0 μm in width. The specific surface area through the mercury porosimetry method and the Brunauer–Emmett–Teller (BET) surface area were estimated to be 5.63 m 2 /g and 8.52–28.44 m 2 /g, respectively. For the test at the initial Pb(II) concentrations of 50, 100, 150 and 200 mg/L, the removal capacities of the un-pulverized SS-HAP/C (>3 mm) were determined to be 52.62, 101.85, 152.08 and 210.69 mg/g, respectively, which were comparable to the adsorption capacities of the synthetic nano-hydroxyapatites. The SS-HAP/C showed an excellent removal performance as an adsorbent for Pb(II) ions. The formation of the (Pbx Ca1‒x )5 (PO4 )3 (OH) solid solution through the coexisting ion exchange (x = 0.01–0.05) and dissolution-precipitation (x = 0.20–0.21) processes was the main mechanism for the Pb(II) uptake. Graphical abstract: Image 1 Highlights: One kind of porous biomorph-genetic composite of HAP/C was prepared. The material retained the hierarchical porous structure of sugarcane top stems. The material has different pores from vessels, parenchyma, sclerenchyma and pits. The adsorption capacity for Pb(II) is comparable to nano hydroxyapatite. The adsorption followed the pseudo-second-order equation and Langmuir isotherm.